Maternal and neonatal outcome in teenage pregnancy - Marimuthu, Kavitha; S., Sivamanju (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Pregnancies that occur below the age of 19 years are called as teenage pregnancies. Teenage pregnancy is a common public health problem worldwide which is harmful to the health of mother and child and has long been considered a high-risk state. It is associated with high maternal, fetal and neonatal mortality and morbidity. The complications are anaemia, preterm delivery, hydramnios, malposition, preeclampsia, eclampsia. Methods: A prospective study of teenage pregnancy was carried out at Government Dharmapuri Medical College, Dharmapuri for the period of 1 year. Pregnant women admitted in labour ward were taken for study. 500 cases of teenage women upto 19 years were included in above period. A structured proforma was used to collect information. Information regarding age, educational status, occupation, socioeconomic status, number of siblings in the family, marital status, age at marriage, health awareness, knowledge about pregnancy and delivery, antenatal visits were obtained from history. Complications during antenatal period, delivery and postpartum were observed. Details regarding mode of delivery and birth weight of the baby were noted. Baby details noted and babies admitted in neonatal ward were followed up till they were discharged. Results: The incidence of teenage pregnancy was 6.74%. In our study 93% of pregnant teenagers were 17-19 years old. Around half had caesarean section. All complications such as anaemia, PIH, preterm, low birth weight and post op complications such as local sepsis, mastitis and UTI were increased in teenage group. Most of babies in the study group required NICU admission. Leading causes of admission in NICU were respiratory distress and preterm babies. Conclusions: Teenage pregnancy is associated with significantly higher risk of anaemia, PIH, preterm deliveries, neonatal mortality and morbidity. A combined multidisciplinary approach involving educationists, health and social workers, obstetrician and gynaecologists is required to improve the adolescent’s reproductive health.